PENDAMPINGAN PENYUSUNAN DESAIN PEMBELAJARAN BERORIENTASI PADA AKM DAN PISA UNTUK GURU - Churun Lu’lu’il Maknun; Rahma Nasir; Manto Lumban Gaol; Uncok Manigor Jokkas Siahaan; Ni Made Intan Kertiyani (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
Based on PISA results, Indonesian students' reading scores are ranked 72 out of 77 participating countries. This minimal ability certainly needs to be overcome, one of which is by increasing the competence of teachers in schools. a total of 40 participants from various regions participated in this service activity which came from various levels, namely elementary, junior high, high school, and vocational school. Agenda for providing materials related to AKM and PISA-based learning designs and evaluation of activities. Based on the evaluation, it was seen that the workshop participants showed a good category attitude through being creative, cooperative, and independent. This AKM and PISA-oriented Learning Design Workshop has benefits for both the participants and the service team. Based on the results of the evaluation in terms of audio and video quality, the material presented by the resource persons, the method of presenting the material and the use of the language of the service team, the workshop was carried out well